Prevalence and predictors of elective and emergency caesarean delivery among reproductive-aged women in Bangladesh: evidence from demographic and health survey, 2017-18 - T. Muhammad; Shobhit Srivastava; Pradeep Kumar; Rashmi Rashmi (BMC, 2022)
Abstract Background Over the years, an increasing trend of unnecessary caesarean section (c-section) deliveries has raised concerns in Bangladesh. So far, many studies have reported the risk factors of c-section delivery in Bangladesh. However, most of these studies did not estimate the predictors of the two c-section procedures (i.e., emergency and elective) separately based on the timing of the c-section decision. This study solely brings forward the role of socio-demographic and economic factors that may be associated differently with emergency and elective c-section deliveries. Methods Data for the study were drawn from the 2017-18 Bangladesh Demographic and Health Survey with 5,299 women aged 15-49 years who gave birth at a health facility during three years preceding the survey. Descriptive statistics along with bivariate analysis were used to fulfill the study objectives. Further, multivariable logistic regression analysis was conducted on binary outcome variables of elective/emergency c-section deliveries. Results Approximately one-third of women in the reproductive-age group opted for delivery through c-section. Out of them, 18.7% of women had elective c-sections, and 14.1% had emergency c-sections. Women who had mass media exposure were 32% more likely to deliver through elective c-sections than women who had no exposure [AOR: 1.32; CI: 1.02-1.72]. Women with higher education had a 56% lower likelihood of delivering through emergency c-section than women with no educational status [AOR: 0.44; CI: 0.24-0.83]. Children from the third or higher birth order were significantly more likely to be delivered through elective c-sections than those from the first birth order [AOR: 2.67; CI: 1.75-4.05]. In contrast, children with higher birth order had fewer chances of emergency c-section than children with first birth order [AOR: 0.29; CI: 0.18 -0.45]. Both elective and emergency c-section deliveries were significantly higher among private health facilities. Conclusion Although c-section delivery has emerged as a life-saving intervention, the overuse of such practice has created lucrative risks for the mother and unborn child. Proper sensitization of mothers and families can enhance the knowledge of the unsafe nature of unnecessary c-section deliveries. Authorizations in case of over-use of elective and emergency c-sections should be observed to minimize the unnecessary c-sections and related complications and to increase normal institutional deliveries in Bangladesh.